Assessment of sex hormone-binding globulin and osteocalcin in patients undergoing coronary artery bypass graft surgery - Kunst, Gudrun; Pfeilschifter, Johannes; Kummermehr, Gunter; Luntz, Steffen P.; Bauer, Harald; Martin, Eike; Motsch, Johann (Journal of cardiothoracic and vascular anesthesia, 2000)
OBJECTIVE: To determine sex hormone-binding globulin (SHBG) and osteocalcin (OC) levels in patients undergoing coronary artery bypass graft surgery to clarify the status of peripheral thyroid metabolism and to correlate SHBG and OC with thyroid hormones and adverse postoperative events. DESIGN: Prospective study. SETTING: University medical center. PARTICIPANTS: Fifty randomly selected patients undergoing coronary artery bypass graft surgery. INTERVENTIONS: On the morning of surgery before induction of anesthesia; 30 minutes after cross-clamping of the aorta; 2 hours and 6 hours after aortic cross-clamp removal; and on the first, second, third, and seventh postoperative mornings, blood samples were drawn and analyzed for OC, SHBG, triiodothyronine (tT3), free T3 (fT3), thyroxine (tT4), free T4 (fT4), thyroid-stimulating hormone, and thyroid-binding globulin. Adverse postoperative events were recorded. MEASUREMENTS AND MAIN RESULTS: Mean tT3 and fT3 decreased on average by 35% and 18% but remained within the normal range perioperatively. Similarly, mean SHBG and OC remained within the normal range. More than half of the patients investigated (60%) had OC concentrations below the normal range. Patients with pathologically decreased tT3 (n = 6) and tT4 (n = 16) intraoperatively and postoperatively had SHBG and OC concentrations similar to those in patients with normal tT3 and tT4 levels. Patients with postoperative complications had significantly lower OC levels preoperatively and on the first postoperative morning than those with an uneventful postoperative recovery. CONCLUSION: Despite significant intraoperative and postoperative decreases in levels of thyroid hormones, low T3 syndrome was rare in this patient population. Unchanged concentrations of SHBG and OC in patients with pathologically decreased tT3 or tT4 suggest normal local thyroid exposure at the tissue sites in these patients. OC may act as a predictor for postoperative outcome.
Gesehen am 01.12.2017